2017
DOI: 10.1016/j.vetpar.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Toxic and repellent activity of selected monoterpenoids (thymol, carvacrol and linalool) against the castor bean tick, Ixodes ricinus (Acari: Ixodidae)

Abstract: The castor bean tick, Ixodes ricinus, is a species of medical and veterinary importance. The use of synthetic acaricides for tick control has led to development of resistance, residues in the environment and animal products, and public health concerns. In this regard, plant essential oils and their main constituents represent an appealing alternative strategy to combat ticks. The phenols thymol and carvacrol and the alcohol linalool are monoterpenoids occurring in essential oils of several aromatic and medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(62 citation statements)
references
References 63 publications
5
49
1
1
Order By: Relevance
“…Moreover, thymol was the major constituent of the essential oil from T. ammi , which is confirmed also by earlier studies . This plant phenol ranks among the most biologically effective compounds when compared with other constituents of essential oils . In addition, it has been demonstrated that thymol is capable of reducing the insect population density even if sublethal doses are applied .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, thymol was the major constituent of the essential oil from T. ammi , which is confirmed also by earlier studies . This plant phenol ranks among the most biologically effective compounds when compared with other constituents of essential oils . In addition, it has been demonstrated that thymol is capable of reducing the insect population density even if sublethal doses are applied .…”
Section: Resultssupporting
confidence: 78%
“…These compounds possess notable insecticidal activity owing to their lipophilicity which enable them to cross easily the insect cuticle and enter the cells. From a mechanistic perspective, thymol is endowed with notable anti‐acetylcholinesterase activity and is reported as GABA A receptor agonist, whereas myristicin is able to inhibit the cytochrome P450 detoxicative enzymes . Thymol has been reported to possess repellent activity and insecticidal effects against various insects such as house fly, red flour beetle, southern corn rootworm, American cockroach, Formosan subterranean termite and mosquitoes .…”
Section: Resultsmentioning
confidence: 99%
“…As an aromatic oxygenated monoterpene, carvacrol is known to be attractive to pollinators (Patricelli et al, 2015). Carvacrol has also antifungal and insecticidal properties (Mendes, 2014;Patricelli et al, 2015;Tabari, Youssefi, Maggi, & Benelli, 2017) and, due to the fact that plants are more sensitive to herbivores and disease at an early vegetative stage, high amounts of carvacrol could be functioning as an allomone. Increasing the carvacrol content in flowers and at the flowering stage demonstrates the role of this phenolic monoterpene as a kairomone (Patricelli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations are reported from other arthropod studies. For example, ivermectin failed to kill the eggs of head lice, and permethrin had limited ovicidal activities against the tick Ixodes ricinus at concentrations that eliminated motile larvae . Only ivermectin has previously been proposed to have limited ovicidal activity on S. scabiei eggs.…”
mentioning
confidence: 99%